My summer of pink & green - Greenwald, Lisa (Amulet Books, 2013)
Rather than a summer of fun transforming her family's pharmacy into an eco-spa, Lucy Desberg must face her sister Claudia's new boyfriend Bean, investor Gary's irritating daughter Bevin, and a spa coordinator who is put in charge of the plans.